Cross-cultural validation of the new version of the Coronavirus Anxiety Scale in twelve Latin American countries - Caycho Rodríguez, Tomás (2022)
The Coronavirus Anxiety Scale (CAS) was recently developed to assess dysfunctional anxiety related to COVID-19. Although different studies reported that the CAS is psychometrically sound, it is unclear whether it is invariant across countries. Therefore, the present study aimed to examine the measurement invariance of the CAS in twelve Latin American countries (Argentina, Bolivia, Chile, Colombia, Cuba, Ecuador, El Salvador, Guatemala, Mexico, Paraguay, Peru, and Uruguay). A total of 5196 people participated, with a mean age of 34.06 (SD = 26.54). Multigroup confirmatory factor analysis (CFA) was used to examine the measurement invariance of the CAS across countries and gender. Additionally, the graded response model (GRM) was used to provide a global representation of the representativeness of the scale with respect to the COVID-19 dysfunctional anxiety construct. The unidimensional structure of the five-item CAS was not confirmed in all countries. Therefore, it was suggested that a four-item model of the CAS (CAS-4) provides a better fit across the twelve countries and reliable scores. Multigroup CFA showed that the CAS-4 exhibits scalar invariance across all twelve countries and all genders. In addition, the CAS-4 items are more informative at average and high levels of COVID-19 dysfunctional anxiety than at lower levels. According to the results, the CAS-4 is an instrument with strong cross-cultural validity and is suitable for cross-cultural comparisons of COVID-19 dysfunctional anxiety symptoms in the general population of the twelve Latin American countries evaluated.